Human dirofilariasis - Unforeseen lesion in subcutaneous nodules: Case series from a tertiary care hospital, Wayanad - M M Gitanjali; Prasannakumar G Konapur; Hasaf Kolakkadan; K Nabeel Azeez (Wolters Kluwer Medknow Publications, 2024)
Human dirofilariasis is a type of zoonotic infection caused by the Dirofilarial species. It is a type of roundworm which is commonly seen in dogs, cats and is transmitted to humans by mosquito bite. Microfilaria is rarely produced in humans. Although clinically they can have varied presentations, it usually presents as ocular or subcutaneous nodules. Definitive diagnosis requires histopathological findings of this worm. We hereby report three cases of Dirofilariasis from a tertiary care hospital in Wayanad.